Unequal Occupational Mobilities Between Rural Migrant and Urban Resident Workers in Urban China - Zhang, Chong (Frontiers in Sociology, 2020)
This study compared the occupational mobilities between rural migrant and urban resident workers in China's urban labour market. I used three heatmaps to visualize the differences between rural migrant and urban resident workers in the outflow distributions of occupational mobility. The result shows a marked disadvantage of rural migrant workers' mobility to the white-collar occupations and a relatively high tendency for them to move to or stay in the manual and agricultural occupations.